Nilai Gizi dan Daya Terima Cookies Ikan Gabus sebagai Makanan Tambahan untuk Ibu Hamil di Kabupaten Sleman, DIY - Eugenius Phyowai Ganap; Riantina Rizky Amalia; Pakartian Ayu Sugmana; Laksmi Ika Hidayati (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2020)
Background: Pregnant women needs more nutri onal intake during pregnancy. Lack of nutri onal intake during pregnancy may leads to malnutri on problems. Therefore, it is necessary to provide supplemetary food (PMT) for pregnant women to meet the nutri onal needs during pregnancy. Objec ve: To nd the best formula on of snakehead sh cookies that are well accepted by pregnant women and to test their nutri onal content and microbiological contamina on. Method: This study is an analy cal survey study begins with the formula on of snakehead sh cookies. The formula on of snakehead sh cookies is made by subs tu ng wheat our with snakehead sh our by 50% and 60%. The acceptance test was carried out on pregnant women in the Sleman District, DIY. Cookies with the best acceptability are then laboratory tested to see their nutri onal content and microbiological contamina on. Results adn Discussion: The average value of all the organolep c parameters of the cookies ranged from 3.41 to 3.91 on a scale of 5. There was no signi cant di erence onorganolep c parameters between the formula 50% and 60% (p<0.05). The snakehead sh cookies have the following nutri onal content per 100 g of cookies: 565.9 kcal energy, 14.09 g protein, 24.33 g fat, 72.62 g carbohydrates, and 2.68% water content. The nutri onal content and microbiological contamina on of snakehead sh cookies have met the quality requirements of supplementary food for pregnant by the Ministry of Health of the Republic of Indonesia. Conclusion: Snakehead sh cookies are quite well accepted by pregnant women. Snakehead sh cookies can be used as an alterna ve supplementary foor for pregnant women. Keywords: Snakehead sh cookies; complementary food for pregnant women; food acceptability